INDUSTRIAL UKRAINE FLUORITE MINERALIZATION IN CONNECTION WITH TECTONIC-MAGMATIC ACTIVIZATION - KURYLO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Geological characteristic of industrial fluorspar deposits and ore manifestation of main fluorspar containing regions in Ukraine are given. Their major geological peculiarities, regularities of location in special structure-tectonic zones are shown.